Necessity of Epigenetic Epidemiology Studies on the Carcinogenesis of Lung Cancer in Never Smokers - Jong-Myon Bae (Korean Society for Preventive Medicine, 2018)
Based on epidemiological and genomic characteristics, lung cancer in never smokers (LCNS) is a different disease from lung cancer in smokers. Based on current research, the main risk factor for LCNS may be air pollution. A recent case-control study in Koreans reported that nitrogen dioxide (NO2) may be a risk factor for LCNS. Additionally, a cohort study showed that exposure to NO2 was associated with significant hypomethylation. Thus, epigenetic epidemiology studies are needed in the near future to evaluate the carcinogenesis of LCNS according to chronic exposure to air pollution and/or viral infections.